Frequency domain synthetic aperture focusing technique for variable-diameter cylindrical components - Jin, Haoran (2017)
Ultrasonic non-destructive testing (UNDT) plays an important role in ensuring the quality of cylindrical components of equipment such as pipes and axles. As the acoustic beam width widens along propagation depths, the diffraction of acoustic wave becomes serious and the images of defects will be interfered with. To precisely evaluate the dimensions of defects and flaws concealed in components, the synthetic aperture focusing technique (SAFT) is introduced to enhance the image resolutions. Conventional SAFTs have been successfully implemented for the ultrasonic imaging of normal cylinders, while solutions for complex ones, such as variable-diameter cylinders, are still lacking. To overcome this problem, a frequency-domain SAFT for variable-diameter cylindrical components is proposed. This algorithm is mainly based on acoustic field extrapolation, which is modified from cylindrical phase shift migration with the aid of split-step Fourier. After a series of extrapolations, a high-resolution ultrasound image can be reconstructed using a particular imaging condition. According to the experimental results, the proposed method yields low side lobes and high resolutions for flat transducers. Its attainable angular resolution relies on the transducer diameter D and scanning radius R and approximates D/(2R).